2023
DOI: 10.3390/educsci13090924
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Computer Science Students’ Perception of ChatGPT in Higher Education: A Descriptive and Correlation Study

Harpreet Singh,
Mohammad-Hassan Tayarani-Najaran,
Muhammad Yaqoob

Abstract: ChatGPT is an emerging tool that can be employed in many activities including in learning/teaching in universities. Like many other tools, it has its benefits and its drawbacks. If used properly, it can improve learning, and if used irresponsibly, it can have a negative impact on learning. The aim of this research is to study how ChatGPT can be used in academia to improve teaching/learning activities. In this paper, we study students’ opinions about how the tool can be used positively in learning activities. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Of those who reported having used ChatGPT, only four students shared that they were caught, that is, that the instructor noticed that they had used ChatGPT for their written assignment. The result regarding the prevalence of use is in line with that of Singh et al (2023) who found that although UK students were generally familiar with the tool, they reported not using it on a regular basis. However, these findings contradict those of Jowarder ( 2023) who found that most US students in his study were familiar with ChatGPT and had indeed used it in their education.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Of those who reported having used ChatGPT, only four students shared that they were caught, that is, that the instructor noticed that they had used ChatGPT for their written assignment. The result regarding the prevalence of use is in line with that of Singh et al (2023) who found that although UK students were generally familiar with the tool, they reported not using it on a regular basis. However, these findings contradict those of Jowarder ( 2023) who found that most US students in his study were familiar with ChatGPT and had indeed used it in their education.…”
Section: Discussionsupporting
confidence: 83%
“…For example, Singh et al (2023) carried out a study using a 12-item questionnaire on 430 university students of computer science in the United Kingdom. The results showed that…”
Section: University Students' Use Of Chatgptmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, these tools can be valuable in delivering timely, efficient, and www.nature.com/scientificreports/ personalized support to a broad student population promoting equity in education [71][72][73][74] . On the other hand, valid concerns should be emphasized including the possible generation of inaccurate and biased educational content among other ethical concerns 1,5,75,76 . Additionally, Safranek et al highlighted the current limitations of ChatGPT in medical education including the inability to provide comprehensive contextual information along with its lack of intuitive patient assessment capabilities which are essential skills acquired during medical education 75 .…”
Section: Discussionmentioning
confidence: 99%
“…This study addresses a well-defined problem that lies at the intersection of technology acceptance, and higher education, exploring the adoption of ChatGPT by students. In this context, recent studies (Rudolph et al, 2023;Shoufan, 2023;Singh et al, 2023) have already provided initial findings on students' perceptions, beliefs and functionalities of ChatGPT, offering foundational insights into its application in educational contexts. Yet, it is essential to consider the temporal dynamics of such adoption due to the evolving nature of interactions with emerging AI chatbots.…”
Section: Introductionmentioning
confidence: 99%